(untitled) (Eurasian Journal of Ecology, 2018)
The article considers the common questions the feasibility of using remote sensing data for the monitoring of some typical and important in terms of pollution of surface water bodies and streams Ili River basin. It is shown that the use of remote sensing methods can cover large areas, to obtain for comparison and analysis of existing trends of multi-temporal information, to map potential sources of hazards to health and life of humans, biota and natural ecosystems of pollutants. The results of the analysis of remote sensing data of the two largest and most important in the hydrological and hydrochemical regard to water bodies-Kapshagai reservoir and Sorbulak wastewater storage show that the use of modern geo-information systems can be an important element of the system of monitoring of surface water status and assessing the impact of pollutants on the quality of water used by the population for domestic use, for technogenic purposes, irrigation, fishery purposes, etc. in the Ile river basin. Using modern methods of remote sensing techniques allows to quickly identify areas of water pollution depending on the presence of contaminants and sediment, changing the properties of surfactants, changes in the spectral characteristics of the display in the images, such as anthropogenic eutrophication of the reservoir, etc. Represented in this article the main approaches to the use of remote sensing methods can be an important part of monitoring the condition of the surface water. Key words: monitoring, water quality, remote sensing, water bodies, pollution.